2012
DOI: 10.1111/j.1749-6632.2012.06648.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of intestinal morphology and GALT by pituitary hormones in the rat

Abstract: Here, the effects of neurointermediate (NIL), anterior (AL), and total hypophysectomy (HYPOX) on ileal mucosa cells and gut-associated lymphoid tissue (GALT) are reported. Compared with the sham-operated (SHAM) rats, the villi height and goblet cells numbers were significantly decreased in all groups. Lamina propria area decreased in AL and HYPOX, but not in NIL animals. CD8(+) but not CD4(+) lymphocytes decreased in the HYPOX and NIL groups. Paneth cells did not change, while IgA cells, IgM cells, and secre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Additionally, GH is also capable to activate human monocytes for an enhanced intermediate ROS production in vitro [51], [52]. We have also reported that HYPOX and NIL, causes increasing bacterial colonization of Peyer patches and spleen, accompanied by a decrease in the intestinal secretory profile of IgA, as well as low IgM and IgG serum levels during the intestinal infection with Salmonella serovar typhimurium [1], [3]. All together this information supports the view that both GH and neurohypophysial hormones might play a role as stimulators/modulators of the immune system in peripheral and gut-associated lymphoid tissue (GALT).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, GH is also capable to activate human monocytes for an enhanced intermediate ROS production in vitro [51], [52]. We have also reported that HYPOX and NIL, causes increasing bacterial colonization of Peyer patches and spleen, accompanied by a decrease in the intestinal secretory profile of IgA, as well as low IgM and IgG serum levels during the intestinal infection with Salmonella serovar typhimurium [1], [3]. All together this information supports the view that both GH and neurohypophysial hormones might play a role as stimulators/modulators of the immune system in peripheral and gut-associated lymphoid tissue (GALT).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are similar in hypophysectomized (HYPOX) rats orally infected with sub-lethal doses of Salmonella serovar typhimurium , which developed an increased colonization of Peyer patches and spleen (Campos-Rodríguez et al, 2006), whereas the intraperitoneal infection was reversed to normal when GH was administrated [30]. In rats subjected to HYPOX, neuro-intermediate pituitary lobectomy (NIL), and anterior pituitary lobectomy (AL), AVP plays an important role as immunomodulatory hormone on innate and acquired immunity [1], [3], [21], [32][34]. Regarding the ileal mucosa-GALT, evidence indicates that in basal conditions, AVP regulates the number of CD4 and CD8 lamina propria lymphocytes, IgM and IgA producing cells, and IgA secretion, as well as intraepithelial CD8+ T cells numbers [1], [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation